2020
DOI: 10.1017/s1368980020001652
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink intake is associated with insomnia and decreased daytime functioning in young adult females

Abstract: Objective: To investigate the association between energy drink (ED) use and sleep-related disturbances in a population-based sample of young adults from the Raine Study. Design: Analysis of cross-sectional data obtained from self-administered questionnaires to assess ED use and sleep disturbance (Epworth Sleepiness Scale, Functional Outcomes of Sleep Questionnaire (FOSQ-10) and the Pittsburgh Sleep Symptoms Questionnaire–Insomnia (PSSQ-I)). Regression modelling was used to estimate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
7
0
4
Order By: Relevance
“…Adolescents who consumed a higher amount of EDs slept less and reported more emotional and behavioural problems. Previous studies confirmed our findings that excessive use of EDs was associated with reduced and insufficient sleep duration [ 20 , 21 , 23 , 50 ] or even insomnia [ 24 ]. The association between insufficient sleep duration and emotional and behavioural problems has also been confirmed by several cross-sectional, experimental studies, as well as by systematic reviews [ 25 , 26 , 37 , 38 , 39 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Adolescents who consumed a higher amount of EDs slept less and reported more emotional and behavioural problems. Previous studies confirmed our findings that excessive use of EDs was associated with reduced and insufficient sleep duration [ 20 , 21 , 23 , 50 ] or even insomnia [ 24 ]. The association between insufficient sleep duration and emotional and behavioural problems has also been confirmed by several cross-sectional, experimental studies, as well as by systematic reviews [ 25 , 26 , 37 , 38 , 39 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Arrows were added to the parallel mediation models in Figures 1 and 2 to illustrate the mediation, expected and tested direction of the associations presented. All analyses were performed in SPSS v. 23 for Windows (IBM Corporation, New York, NY, USA). method, and bootstrapped 95% confidence intervals for the indirect effect of ab was provided as a test of the indirect effect [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Again according to the data analysis, it is reasonable to say that the consump- tion of EDs is a widespread phenomenon affecting different age groups and various segments of the population. The frequency of consumption of EDs has been found to be statistically significantly associated with insomnia, also reported by several studies (Marmorstein, 2017;Trapp et al, 2020) and the risk of alcohol abuse, mentioned by others (Marmorstein, 2017;Meredith et al, 2016;Arria et al, 2011). We identified the level of depression as not being related to the amount of EDs consumed by the respondents; the same result was shown in the study of Arria et al (2011), but there are also a number of studies in the literature showing a relationship between depression and the consumption of EDs (Evren & Evren, 2015;Azagba et al, 2014;Hofmeister et al, 2010).…”
Section: • 4 Discussionsupporting
confidence: 68%